Earth summit ethics : toward a reconstructive postmodern philosophy of environmental education - Callicott, J. Baird; Rocha, Fernando J. R. da, 1943- (SUNY series in constructive postmodern thought., 1996)
On the eve of the 1992 Earth Summit in Rio de Janeiro, Fernando J.R. da Rocha challenged environmental philosophers to suggest and develop effective ways in which universities might engender ecological literacy and environmental ethics. The result was a pre-conference held in Porto Alegre, Brazil, whose aim was to put the summit in philosophical perspective, influence its outcome, and chart a new course, linking environment and ethics through university education. This book is an outgrowth of the Porto Alegre conference, and the international environmental philosophers and educators represented here inaugurate a constructive dialogue that will continue well into the twenty-first century. Among the contributors to the volume are environmental philosophers Andrew Brennan, J. Baird Callicott, Fernando J.R. da Rocha, and Holmes Ralston, III, and education theorists Peter Madsen and John Lemons. In addition, the book introduces English-language readers to the work of French philosopher Catherine Larrere, Spanish philosopher Nicholas Sosa, and Brazil's radical former Secretary for the Environment and deep ecologist Jose Lutzenberger.